Stroke-associated pneumonia with low PaO2/FiO2 ratio in acute large vessel occlusion after endovascular therapy: risk factors and prognosis - Tang, Kun; Li, Jia; Wang, Yucheng; Guo, Zhangbao; Yang, Yun; Guo, Fangliang; Cai, Yin; Liu, Wenhua (Frontiers in neurology, 2025)
Stroke-associated pneumonia (SAP) often occurs after ischemic stroke. A deterioration in SAP manifests itself in a decreased partial pressure oxygen (PaO2)/fraction of inspired oxygen (FiO2) ratio, indicating gas exchange dysfunction. We aimed to investigate independent predictors and outcomes of SAP with low PaO2/FiO2 ratio among patients with acute large vessel occlusion (ALVO) undergoing endovascular therapy.BackgroundStroke-associated pneumonia (SAP) often occurs after ischemic stroke. A deterioration in SAP manifests itself in a decreased partial pressure oxygen (PaO2)/fraction of inspired oxygen (FiO2) ratio, indicating gas exchange dysfunction. We aimed to investigate independent predictors and outcomes of SAP with low PaO2/FiO2 ratio among patients with acute large vessel occlusion (ALVO) undergoing endovascular therapy.We retrospectively analyzed the prospective data of consecutive adult post-interventional patients with ALVO admitted to neuro-intensive care units in Wuhan No. 1 Hospital from December 2020 to December 2022. Patients developing SAP without coronavirus disease 2019 were included in this study and divided into two subgroups: PaO2/FiO2 ratio > 240 and ≤ 240. The primary outcome was favorable neuro-function at 90 days (modified Rankin Scale score of 0-2). Secondary outcomes included hospitalization days, occurrence of symptomatic intracerebral hemorrhage, and 90-day mortality. The independent risk factors and prognosis for SAP with PaO2/FiO2 ratio ≤ 240 were identified by logistic regression analyses.MethodsWe retrospectively analyzed the prospective data of consecutive adult post-interventional patients with ALVO admitted to neuro-intensive care units in Wuhan No. 1 Hospital from December 2020 to December 2022. Patients developing SAP without coronavirus disease 2019 were included in this study and divided into two subgroups: PaO2/FiO2 ratio > 240 and ≤ 240. The primary outcome was favorable neuro-function at 90 days (modified Rankin Scale score of 0-2). Secondary outcomes included hospitalization days, occurrence of symptomatic intracerebral hemorrhage, and 90-day mortality. The independent risk factors and prognosis for SAP with PaO2/FiO2 ratio ≤ 240 were identified by logistic regression analyses.A total of 159 subjects developing SAP were included in this study: 53 with PaO2/FiO2 ratio > 240 and 106 with ratio ≤ 240. Compared to subjects with PaO2/FiO2 ratio > 240, those with PaO2/FiO2 ratio ≤ 240 had older ages, higher baseline National Institutes of Health Stroke Scales scores, larger proportions of baseline Glasgow Coma Scale (GCS) score of 3-8 and grade of kobuta water swallow test ≥ 3, higher white blood cell (WBC) counts (all p values <0.05). The independent predictors for SAP with PaO2/FiO2 ratio ≤ 240 included ages (adjusted odds ratio [OR], 1.043; 95% confidential interval [CI], 1.011-1.077; p = 0.009), baseline GCS scores of 3-8 (adjusted OR, 2.802; 95% CI, 1.214-6.465; p = 0.016), and ln-transformed WBC counts after SAP diagnosis (adjusted OR, 3.977; 95% CI, 1.226-12.896; p = 0.021). SAP with PaO2/FiO2 ratio ≤ 240 was robustly associated with longer hospitalization days (adjusted OR, 1.074; 95% CI, 1.01-1.143; p = 0.024).ResultsA total of 159 subjects developing SAP were included in this study: 53 with PaO2/FiO2 ratio > 240 and 106 with ratio ≤ 240. Compared to subjects with PaO2/FiO2 ratio > 240, those with PaO2/FiO2 ratio ≤ 240 had older ages, higher baseline National Institutes of Health Stroke Scales scores, larger proportions of baseline Glasgow Coma Scale (GCS) score of 3-8 and grade of kobuta water swallow test ≥ 3, higher white blood cell (WBC) counts (all p values <0.05). The independent predictors for SAP with PaO2/FiO2 ratio ≤ 240 included ages (adjusted odds ratio [OR], 1.043; 95% confidential interval [CI], 1.011-1.077; p = 0.009), baseline GCS scores of 3-8 (adjusted OR, 2.802; 95% CI, 1.214-6.465; p = 0.016), and ln-transformed WBC counts after SAP diagnosis (adjusted OR, 3.977; 95% CI, 1.226-12.896; p = 0.021). SAP with PaO2/FiO2 ratio ≤ 240 was robustly associated with longer hospitalization days (adjusted OR, 1.074; 95% CI, 1.01-1.143; p = 0.024).SAP with PaO2/FiO2 ratio ≤ 240 is shown in significant relevance to the prolonged in-hospital stays among post-interventional patients. Older ages, baseline GCS scores of 3-8, and higher WBC counts after SAP diagnosis can independently predict the occurrence of SAP with a lower PaO2/FiO2 ratio. Further validation studies are needed.ConclusionSAP with PaO2/FiO2 ratio ≤ 240 is shown in significant relevance to the prolonged in-hospital stays among post-interventional patients. Older ages, baseline GCS scores of 3-8, and higher WBC counts after SAP diagnosis can independently predict the occurrence of SAP with a lower PaO2/FiO2 ratio. Further validation studies are needed.